The effect of first school years on mathematical skill profiles - Nanu Cristina; Laakkonen Eero; Hannula-Sormunen Minna (European Association for Research on Learning and Instruction, 2022)
This study investigated the effect of children’s first formal school years on mathematical skill profiles, measured by a variety of arithmetical skills and Spontaneous Focusing On Numerosity (SFON) tasks. By using person-centered approach the aim was to investigate whether the amount of formal schooling is associated with mathematical skills in the same way for all children, or, whether the associations differ according to the children’s mathematical skill profiles. Data was analyzed from 652 4–7-year-old children from four European countries with different school entrance ages. A person-centered approach with latent profile regression analyses on four-factor score variables identified six mathematical skill profiles with both qualitative and quantitative differences. The results revealed significant, but small effects of the amount of schooling on mathematical profiles when chronological age and country-specific school entrance age were controlled for. Educational implications of the findings emphasize regarding the heterogeneity in children’s mathematical skill profiles and the potentially different effects of starting formal schooling across different profiles.